2020 IEEE/OES Autonomous Underwater Vehicles Symposium (AUV)(50043) 2020
DOI: 10.1109/auv50043.2020.9267933
|View full text |Cite
|
Sign up to set email alerts
|

CFD-FSI Analysis on Motion Control of Bio-Inspired Underwater AUV System Utilizing PID Control

Abstract: For the design of a bio-inspired, fish-like robot with caudal fin, a Fluid Structure Interaction (FSI) analysis has been conducted to investigate the influence of material properties and undulation kinematics on hydrodynamic performance and efficiency. This supports the design process with focus on practical prototype build up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Furthermore, Wright et al [97] utilized FSI analysis to investigate how the material properties of robotic fish caudal fins affect hydrodynamic performance and efficiency. In a distinctive approach, Li et al [98] studied live pufferfish and developed a numerical model, integrating CFD with multibody dynamics.…”
Section: Biomimetic Robotic Fish Propulsionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Wright et al [97] utilized FSI analysis to investigate how the material properties of robotic fish caudal fins affect hydrodynamic performance and efficiency. In a distinctive approach, Li et al [98] studied live pufferfish and developed a numerical model, integrating CFD with multibody dynamics.…”
Section: Biomimetic Robotic Fish Propulsionmentioning
confidence: 99%
“…Overall, CFD numerical simulations have played a crucial role in exploring the hydrodynamic performance of robotic fish and biomimetic underwater vehicles. From the realistic fish-shaped geometric models developed using OpenFOAM by Khan et al [94] to the FSI analysis of robotic fish caudal fin material properties by Wright et al [97], and the study of fish schooling behaviorʹs hydrodynamics conducted by Li et al [104] (as shown in Figure 5), each study significantly contributes to enhancing our understanding of the hydrodynamics of underwater vehicles. Moreover, these studies also emphasize the immense potential for technological integration.…”
Section: Biomimetic Robotic Fish Propulsionmentioning
confidence: 99%